The Position of Women in Islamic History - Ahmad Musta'id (Institute of Research and Community Service UIN Prof. K.H. Saifuddin Zuhri, 2023)
Before the arrival of Islam, they are known as the jahiliyyah. It shows a historical fact that the position of women is always placed in the position of objects and occupies the second position after men. The position of women is considered less favorable, so women are often used as objects of exploitation that exceed human limits. Then Islam came with teachings that respect the position of women in various aspects of life. The existence of a long journey about the position of women is interesting to analyze and important to study in depth. This research is an Islamic social history research using historical research methods: Heuristics, Verification, Interpretation, and Historiography. At this stage, the author presents the results of the synthesis obtained. This study aims to enrich the historical treasures of Islamic civilization related to the development of the position of women. However, the dynamics of the development of women's position also have many scientific sources that need to be studied more comprehensively. That is, we need to look at events far back to be able to analyze the dynamics of women's positions. The conclusion of this paper explains that in pre-Islamic perspectives starting from Greek, Roman, Jewish, Hindu, and Chinese civilizations, as well as pre-Islamic Arabs, it shows that women occupy a position as inferior until then Islam comes to change their social status with the concept of equality.